Consumption of low‐calorie sweetened beverages is associated with higher total energy and sugar intake among children, NHANES 2011–2016. Issue 10 (2nd May 2019) - Sylvetsky, Allison C.; Figueroa, Janet; Zimmerman, Talia; Swithers, Susan E.; Welsh, Jean A.
Summary: Objective: To examine associations between consumption of low‐calorie sweetened beverages (LCSBs), sugar, and total energy intake in children in the United States. Methods: We used 24‐hour dietary recalls from 7026 children enrolled in the National Health and Nutrition Examination Survey (NHANES) 2011 to 2016 to assess energy and macronutrient intake among LCSB (≥4 oz LCSB, <4 oz SB), SB (≥4 oz SB, <4 oz LCSB), and LCSB + SB consumers (≥4 oz each) compared with water consumers (≥4 oz water, <4 oz LCSB and SBs). Sample weights and complex survey procedures were used for all analyses. Results: Adjusting for body mass index (BMI) percentile, LCSB, SB, and LCSB + SB consumption was associated with 196, 312, and 450 more total calories and 15, 39, and 46 more grams of added sugar, which amounts to 60, 156, 184 more calories from added sugar, compared with water consumers ( P < .05 for all pairwise comparisons). No differences in energy intake were observed between LCSB and SB consumers. [Correction added on 28 May 2019, after first online publication: In the preceding sentence, quantities of added sugar reported are in grams. The corresponding calories have also been specified in this version.] Conclusions: These findings challenge the utility of LCSB for weight management in children and adolescents.